2007
DOI: 10.1029/2006jc003701
|View full text |Cite
|
Sign up to set email alerts
|

Shoaling and shoreline dissipation of low‐frequency waves

Abstract: [1] The growth rate, shoreline reflection, and dissipation of low-frequency waves are investigated using data obtained from physical experiments in the Delft University of Technology research flume and by parameter variation using the numerical model Delft3D-SurfBeat. The growth rate of the shoaling incoming long wave varies with depth with an exponent between 0.25 and 2.5. The exponent depends on a dimensionless normalized bed slope parameter b, which distinguishes between a mild-slope regime and a steep-slop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
228
1
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(254 citation statements)
references
References 38 publications
(61 reference statements)
22
228
1
3
Order By: Relevance
“…Its amplitude then starts to decrease (j to k), while its shape evolves toward a sawtooth profile. These transformations, resembling the behavior of typical inner surf-zone waves, has been identified by van Dongeren et al (2007) as infragravity-wave breaking. The nonlinear transformations of the IG wave are characterized further in Figure 4, which shows the cross-shore evolution of the wave skewness (Sk) and the asymmetry (As) in the surf zone.…”
Section: Nonlinear Wave Transformationmentioning
confidence: 83%
See 3 more Smart Citations
“…Its amplitude then starts to decrease (j to k), while its shape evolves toward a sawtooth profile. These transformations, resembling the behavior of typical inner surf-zone waves, has been identified by van Dongeren et al (2007) as infragravity-wave breaking. The nonlinear transformations of the IG wave are characterized further in Figure 4, which shows the cross-shore evolution of the wave skewness (Sk) and the asymmetry (As) in the surf zone.…”
Section: Nonlinear Wave Transformationmentioning
confidence: 83%
“…In this paper, we focus on the experiment A-1 analyzed in van Dongeren et al 2007, where a very low reflection coefficient (R~0.1) of the infragravity waves was observed at the shoreline. Bichromatic waves of primary frequency f 1 =0.6714 Hz and f 2 =0.4761 Hz, and amplitudes a 1 =0.06 m a 2 =0.012 m were generated on the horizontal part of the beach and were then propagating and breaking over a 1:35 sloping beach.…”
Section: Numerical Set-upmentioning
confidence: 99%
See 2 more Smart Citations
“…While there has been significant work on the characteristics of the generated infragravity wave environment (e.g. van Dongeren et al 2007), investigation of the dissipation of the wave groups themselves has been lacking. Svendsen and Veeramony (2001) showed that some aspect of the wave group structure does survive the breaking process and is indeed seen in the surf zone; however, while they investigated the occurrence of breaking, they did not look into quantifying the level of dissipation in these wave groups.…”
Section: Wave Groupsmentioning
confidence: 99%